1987
DOI: 10.1104/pp.84.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine Synthesis in Castor Bean Endosperm

Abstract: Endosperm halves from 3-day-old castor bean (Ricinus communis var Hale) were incubated for 30 minutes with L-14Cjserine, after which label was observed in ethanolamine, choline, phosphatidylserine, phosphatidylethanolamine, phosphatidylcholine, ethanolaminephosphate, and CDPethanolamine, but not in cholinephosphate or CDPcholine. Only later did significant amounts of isotope become incorporated into cholinephosphate and CDPcholine. The choline kinase inhibitor hemicholinium-3 prevented the incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
17
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 5 publications
7
17
0
Order By: Relevance
“…The ratios of glycine:serine and glutamate:aspartate increased dramatically (>10-fold) in response to AOA (Table II). These responses appear consistent with AOA inhibition of glycine decarboxylase (30,37) and glutamate:oxaloacetate aminotransferase (9 (4,18) and aspartate conversion to asparagine via asparaginesynthetase [20,23]). …”
Section: Resultssupporting
confidence: 72%
“…The ratios of glycine:serine and glutamate:aspartate increased dramatically (>10-fold) in response to AOA (Table II). These responses appear consistent with AOA inhibition of glycine decarboxylase (30,37) and glutamate:oxaloacetate aminotransferase (9 (4,18) and aspartate conversion to asparagine via asparaginesynthetase [20,23]). …”
Section: Resultssupporting
confidence: 72%
“…These results could therefore be due to artifactual decarboxylation of the type that occurs in soluble plant extracts with Ser and other amino acids (Birecka et al, 1985;Rontein et al, 2001). The results of radiotracer kinetic studies with plant tissues fed [U-14 C]Ser are consistent with the presence of PSD activity but do not unambiguously establish its existence (Marshall and Kates, 1974;Kinney and Moore, 1987a;Mudd and Datko, 1989).Plant membranes are known to contain small amounts of Ptd-Ser (Mudd, 1980), and two different plant enzymes that synthesize Ptd-Ser have been identified. Ptd-Ser synthase has been cloned from wheat (Triticum aestivum; Delhaize et al, 1999) providing strong evidence that the yeast-type pathway (Carman and Zeimetz, 1996) for Ptd-Ser synthesis exists in plant tissues.…”
supporting
confidence: 67%
“…These results could therefore be due to artifactual decarboxylation of the type that occurs in soluble plant extracts with Ser and other amino acids (Birecka et al, 1985;Rontein et al, 2001). The results of radiotracer kinetic studies with plant tissues fed [U-14 C]Ser are consistent with the presence of PSD activity but do not unambiguously establish its existence (Marshall and Kates, 1974;Kinney and Moore, 1987a;Mudd and Datko, 1989).…”
supporting
confidence: 65%
“…It is therefore interesting that modeling of the [ 14 C]formate data indicated that the EA moiety of Ptd-EA came from a P-EA pool of low specific activity and from another source, also of low specific activity. This other source could be Ptd-Ser decarboxylation or a base exchange reaction between free EA and phospholipids (Kinney and Moore, 1987;Mudd and Datko, 1989c). Consistent with these possibilities, preliminary analyses showed that 14 C was present in products with the chromatographic properties of Ptd-Ser and free EA.…”
Section: The Origin Of Easupporting
confidence: 56%